Thermoregulation during incremental exercise in masters cycling - Arfaoui, A.; Bertucci, W. M.; Letellier, T.; Polidori, G. (Journal of Science and Cycling, 2013)
This article follows a recently published work (Bertucci et al. 2012) on the effects of age on observed asymmetry during the mechanical process of pedaling for masters cyclists who concern the majority of practitioners. The present work focuses first the link it may exist between muscle mechanical imbalance and skin temperature imbalance. It is shown that the Infrared thermography has not been able to confirm the mechanical asymmetries observed in the previous study. Moreover, a special attention has been paid on the possible relationship between the muscular skin temperature and the heart rate of subjects. Eleven male master cyclists were volunteers to participate to this study. Mapping of skin temperatures of active members (gastrocnemius muscle) was during a graded exercise using the infrared thermography. The skin temperature of calves decreased as the subjects started the exercise and during exercise. Skin temperature distribution presents hyperthermal spots due to the presence of perforator vessels who reach the surface of skin. These spots have been highlighted during exercise. Correlation was found between heart rate and skin temperature evolutions during incremental exercise. Similar trends in the evolution of these two parameters have been highlighted at the origin of each power level.